Measurement of associated Z + charm production in proton–proton collisions at $$\sqrt{s} = 8$$ s=8 $$\,\text {TeV}$$ TeV - A. M. Sirunyan; A. Tumasyan; W. Adam; F. Ambrogi; E. Asilar; T. Bergauer; J. Brandstetter; E. Brondolin; M. Dragicevic; J. Erö; M. Flechl; M. Friedl; et al. (European Physical Journal C: Particles and Fields, 2018)
Abstract A study of the associated production of a $$\mathrm{Z} $$ Z boson and a charm quark jet ($$\mathrm{Z} + \mathrm{c} $$ Z+c ), and a comparison to production with a $$\mathrm{b} $$ b quark jet ($$\mathrm{Z} + \mathrm{b} $$ Z+b ), in $$\mathrm {p}\mathrm {p}$$ pp collisions at a centre-of-mass energy of 8$$\,\text {TeV}$$ TeV are presented. The analysis uses a data sample corresponding to an integrated luminosity of 19.7$$\,\text {fb}^{-1}$$ fb-1 , collected with the CMS detector at the CERN LHC. The $$\mathrm{Z} $$ Z boson candidates are identified through their decays into pairs of electrons or muons. Jets originating from heavy flavour quarks are identified using semileptonic decays of $$\mathrm{c} $$ c or $$\mathrm{b} $$ b flavoured hadrons and hadronic decays of charm hadrons. The measurements are performed in the kinematic region with two leptons with $$p_{\mathrm {T}} ^{\ell } > 20\,\text {GeV} $$ pTℓ>20GeV , $${|\eta ^{\ell }|} < 2.1$$ |ηℓ|<2.1 , $$71< m_{\ell \ell } < 111\,\text {GeV} $$ 71<mℓℓ<111GeV , and heavy flavour jets with $$p_{\mathrm {T}} ^{\text {jet}} > 25\,\text {GeV} $$ pTjet>25GeV and $${|\eta ^{ \text {jet}}|} < 2.5$$ |ηjet|<2.5 . The $$\mathrm{Z} + \mathrm{c} $$ Z+c production cross section is measured to be $$\sigma (\mathrm {p}\mathrm {p}\rightarrow \mathrm{Z} + \mathrm{c} + X) \mathcal {B}(\mathrm{Z} \rightarrow \ell ^+\ell ^-) = 8.8 \pm 0.5\,\text {(stat)} \pm 0.6\,\text {(syst)} \,\text {pb} $$ σ(pp→Z+c+X)B(Z→ℓ+ℓ-)=8.8±0.5(stat)±0.6(syst)pb . The ratio of the $$\mathrm{Z} + \mathrm{c} $$ Z+c and $$\mathrm{Z} + \mathrm{b} $$ Z+b production cross sections is measured to be $$\sigma (\mathrm {p}\mathrm {p}\rightarrow \mathrm{Z} + \mathrm{c} + X)/\sigma (\mathrm {p}\mathrm {p}\rightarrow \mathrm{Z} + \mathrm{b} + X) = 2.0 \pm 0.2\,\text {(stat)} \pm 0.2\,\text {(syst)} $$ σ(pp→Z+c+X)/σ(pp→Z+b+X)=2.0±0.2(stat)±0.2(syst) . The $$\mathrm{Z} + \mathrm{c} $$ Z+c production cross section and the cross section ratio are also measured as a function of the transverse momentum of the $$\mathrm{Z} $$ Z boson and of the heavy flavour jet. The measurements are compared with theoretical predictions.